"To Have and Have Not": Migration, Remittances, Poverty and Inequality in Algeria - David N. Margolis; Luis Miotti; El Mouhoub Mouhoud; Joël Oudinet (Institute for the Study of Labor (IZA), 2013)
This article analyses the distributional impact of remittances across two regions of Algerian emigration (Nedroma and Idjeur) using an original survey we conducted of 1,200 households in 2011. Remittances and especially the role played by foreign pensions decrease the Gini index by nearly 4 % for the two Algerian regions, with the effect in Idjeur being twice as large as Nedroma. At the same time, they help reduce poverty by nearly 13 percentage points. Remittances have a strong positive impact on very poor families in Idjeur but much less in Nedroma, where poor families suffer from a double loss due to the absence of their migrants and the fact that the latter do not send money home.
Keywords: F24; O15; O55; 330; remittances; migration; poverty; inequality; Algeria